Relationship Between P Wave Peak Time In Leads II And V1 With Left Ventricle Diastolic Function In Hypertension Patients - Ihsan, Muhammad; Akbar, Nizam Zikri; Lubis, Hilfan Ade Putra (Journal of Society Medicine, 2023)
Introduction: Left ventricular diastolic dysfunction is common in patients with hypertension. Inadequate management can cause complications such as hypertensive heart disease. Electrocardiography as a tool that is easy to find in health services is known to be able to detect left ventricular diastolic dysfunction. The purpose of this study was to examine the relationship between P wave peak time in leads II and V1 by electrocardiography with left ventricular diastolic function. Method: This study was a cross-sectional study that was conducted by collecting 111 patients with a history of hypertension at RSUP HAM from October 2021 to November 2022. The P wave peak time was measured in leads II and V1 on the ECG. Diastolic function was assessed using echocardiography. A bivariate test was performed to assess the correlation between the two variables. Furthermore, ROC analysis was performed to assess the P wave peak time as a predictor of left ventricular diastolic function. Results: : Total subjects were 111 hypertensive patients consisting of 49 (31.4%) hypertensive patients with normal diastolic function and 62 (68.6%) hypertensive patients with diastolic dysfunction. In bivariate analysis, a significant difference was found between the P wave peak time in lead II of hypertensive patients with normal diastolic function and hypertensive patients with diastolic dysfunction (65.47± 2.5 vs 68.9 ± 2.7;p = 0.001). Based on the ROC analysis, it was found that the P wave peak time could predict left ventricular diastolic dysfunction in hypertensive patients with AUC = 0.81 in lead II. Conclusion: The P wave peak time in lead II can be a predictor of diastolic dysfunction in hypertensive patients.